Engineering Core Size of InP Quantum Dot with Incipient ZnS for Blue Emission. Issue 7 (12th February 2022) - Suh, Yo‐Han; Lee, Sanghyo; Jung, Sung‐Min; Bang, Sang Yun; Yang, Jiajie; Fan, Xiang‐Bing; Zhan, Shijie; Samarakoon, Chatura; Jo, Jeong‐Wan; Kim, Yoonwoo; Choi, Hyung Woo; Occhipinti, Luigi G.; et al.
Abstract: Blue indium phosphide quantum dot (InP QD) is an emerging colloidal semiconductor nanocrystal, considered as a promising next‐generation photoactive material for light‐emitting purposes. Despite the tremendous progress in blue InP QDs, the synthetic method for tailoring InP core size to realize the blue‐emissive QDs still lags behind. This work suggests a synthetic method for blue‐emitting InP QDs by engineering the core size with an incipient ZnS (i‐ZnS) shell. The formation of i‐ZnS complexes, before the tris(trimethylsilyl)phosphine injection (e.g., before core growth process), restrains the overgrowth of InP nuclei by rapidly forming a ZnS shell on its surface, thereby resulting in further dwarfed InP cores. With additional ZnS shell coating, the blue QDs exhibit a photoluminescence quantum yield of ≈52% at 483 nm. The origin of bandgap diminution with the increase of shell thickness, or with the utilization of ZnSe shell is unraveled via the first‐principles density functional theory simulations. Simulational evidence on InP‐core densification with the shell coating, along with accompanying changes in chemical and structural properties, is presented. The blue‐emitting InP QD device shows a maximum luminance of 1162 cd m −2 and external quantum efficiency of 1.4%. Abstract : Blue‐emitting indium phosphide (InP) quantum dots are synthesized by engineering the core size with an incipient ZnS (i‐ZnS) shell. The formation of i‐ZnS complexes restrains the overgrowth of InP nuclei by rapidly forming a ZnS shell on its surface, thereby resulting in further dwarfed InP cores. The origin of this finding is unraveled via the first‐principles density functional theory simulations.